2021
DOI: 10.14704/web/v18si04/web18129
|View full text |Cite
|
Sign up to set email alerts
|

E-Banking Service Quality and Customer Satisfaction: Evidence from Deposit Money Bank in South-South Nigeria

Abstract: The study examines the connection between Electronic Banking service quality and customer satisfaction. The study used a survey research approach. 344 participants were selected randomly for the study. The data from 302 respondents suggest that E-banking service quality dimensions (innovation, technology competence, reliability and tangibility jointly influence customer satisfaction. Further, innovation, technology competence, reliability and tangibility had positive and significant effects on customer satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Our fi showed that both SQ and CE positively impacted CS. Our first finding is in line wit obtained by prior researchers [65][66][67]. In addition, Khan and Fasih (2014) [68] carr research on the banking industry in Bangladesh and discovered that SQ has a sub association with CS.…”
Section: Discussion Of the Findingssupporting
confidence: 91%
“…Our fi showed that both SQ and CE positively impacted CS. Our first finding is in line wit obtained by prior researchers [65][66][67]. In addition, Khan and Fasih (2014) [68] carr research on the banking industry in Bangladesh and discovered that SQ has a sub association with CS.…”
Section: Discussion Of the Findingssupporting
confidence: 91%